-15=9+4(f-2)

Simple and best practice solution for -15=9+4(f-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15=9+4(f-2) equation:



-15=9+4(f-2)
We move all terms to the left:
-15-(9+4(f-2))=0
We calculate terms in parentheses: -(9+4(f-2)), so:
9+4(f-2)
determiningTheFunctionDomain 4(f-2)+9
We multiply parentheses
4f-8+9
We add all the numbers together, and all the variables
4f+1
Back to the equation:
-(4f+1)
We get rid of parentheses
-4f-1-15=0
We add all the numbers together, and all the variables
-4f-16=0
We move all terms containing f to the left, all other terms to the right
-4f=16
f=16/-4
f=-4

See similar equations:

| Z=91-27i | | 3n/6=3/8 | | m^2-14m+50=0 | | 5/9x=45 | | 103=3y^2-5 | | -16=-2d-8d | | -x=3/7 | | 4(-2x+1)=-36 | | -x=3/ | | 15-3x+5=-5x-10+7x | | x2+3x=2x+20 | | 5-7n=11-n | | u−3=3 | | 3^(-x+4)=76 | | -17-7c=2(9c-4) | | 8x÷8=2x÷62 | | A=5x+23 | | 4x-16=-6x+8 | | 21=b|8 | | 7x+96=189 | | 11=y/9+2 | | 2x+21=x+17 | | (X+5)(x+2)—3(4x—3)=(5—x)^2 | | -6+8(1+7s)=-30 | | (2x/3)+1/2=5/6 | | 4x+11=×+2 | | -5h+3h=23 | | 2x-22=140 | | 36-3y=6y | | 3(3w+10)/2=-10 | | -9x+4+5x=25 | | Y=-12+8x |

Equations solver categories